Refining the Balance of Attenuation and Immunogenicity of Respiratory Syncytial Virus by Targeted Codon Deoptimization of Virulence Genes - Jia Meng (American Society for Microbiology, 2014)
ABSTRACT Respiratory syncytial virus (RSV) is the most important pathogen for lower respiratory tract illness in children for which there is no licensed vaccine. Live-attenuated RSV vaccines are the most clinically advanced in children, but achieving an optimal balance of attenuation and immunogenicity is challenging. One way to potentially retain or enhance immunogenicity of attenuated virus is to mutate virulence genes that suppress host immune responses. The NS1 and NS2 virulence genes of the RSV A2 strain were codon deoptimized according to either human or virus codon usage bias, and the resulting recombinant viruses (dNSh and dNSv, respectively) were rescued by reverse genetics. RSV dNSh exhibited the desired phenotype of reduced NS1 and NS2 expression. RSV dNSh was attenuated in BEAS-2B and primary differentiated airway epithelial cells but not in HEp-2 or Vero cells. In BALB/c mice, RSV dNSh exhibited a lower viral load than did A2, and yet it induced slightly higher levels of RSV-neutralizing antibodies than did A2. RSV A2 and RSV dNSh induced equivalent protection against challenge strains A/1997/12-35 and A2-line19F. RSV dNSh caused less STAT2 degradation and less NF-κB activation than did A2 in vitro. Serial passage of RSV dNSh in BEAS-2B cells did not result in mutations in the deoptimized sequences. Taken together, RSV dNSh was moderately attenuated, more immunogenic, and equally protective compared to wild-type RSV and genetically stable. IMPORTANCE Respiratory syncytial virus (RSV) is the leading cause of infant viral death in the United States and worldwide, and no vaccine is available. Live-attenuated RSV vaccines are the most studied in children but have suffered from genetic instability and low immunogenicity. In order to address both obstacles, we selectively changed the codon usage of the RSV nonstructural (NS) virulence genes NS1 and NS2 to the least-used codons in the human genome (deoptimization). Compared to parental RSV, the codon-deoptimized NS1/NS2 RSV was attenuated in vitro and in mice but induced higher levels of neutralizing antibodies and equivalent protection against challenge. We identified a new attenuating module that retains immunogenicity and is genetically stable, achieved through specific targeting of nonessential virulence genes by codon usage deoptimization.